Effect of seedling age and plant hormones on growth and bulb yield of onion (Allium cepa) - CHOUDHARY, DESH RAJ; KUMAR, SATESH; SAMNOTRA, R K (The Indian Journal of Agricultural Sciences, 2016)
The response of three seedling age (6, 8 and 10 week old seedling) of onion (Allium cepa L.) cultivar N 53 was studied against different plant hormonal treatments, viz. Cycocel (500 and 1000 ppm), Ethephon (2 000 and 2 500 ppm) and Paclobutrazol (1 000 and 2 000 ppm) along with control in factorial RBD with three replication during rabi season of 2014-15. Three consecutive foliar sprays of each plant hormone was done at 30, 60 and 90 days after transplanting (DAS). The results showed that 10 week old seedlings out performed other aged seedlings with highest vegetative characters like plant height at 70 and 100 DAT (42.64 and 63.46 cm), number of leaves/plant at 70 and 100 DAT (5.45 and 9.34), leaf length at harvest (62.34 cm) and plant establishment (86.95%). Data with respect to yield attributes clearly pointed out that 8 week old seedlings performed better and showed statistically highest bulb size (25.34 cm2), bulb weight (94.44g) and marketable yield (205.40q/ha). All plant hormones significantly reduce vegetative growth as compared to control. Paclobutrazol 2 000ppm was found statistically superior in increasing bulb size (25.11 cm2), bulb weight (80.73 g) and marketable yield (190.38 q/ha) as compared to other treatments. Interaction between transplanting of 8 week old seedlings and spray of Paclobutrazol 2 000 ppm produced maximum bulb size (32.13 cm2), bulb weight (110.93 g) and marketable yield (279.50 q/ha). The maximum benefit: cost ratio (4.4:1) was obtained by transplanting of 8 week old seedlings and sprayed with Paclobutrazol 2 000 ppm.